Pengaruh Pembinaan Kedisiplinan Dalam Proses Belajar Mengajar Terhadap Etos Kerja Guru SDN 16 Bulu Tellue Kecamatan Tondong Tallasa Kabupaten Pangkep - Hamka Hamka; Muhammad Azis; Rego Devilla (STKIP Andi Matappa Pangkep, 2022)
This study aims to determine the influence of disciplinary development in the teaching and learning process on the work ethic of teachers at SDN 16 Bulu Tellue Kecamatan Tondong Tallasa Kabupaten Pangkep. The method that researchers use is quantitative research with a descriptive approach. Data collection with closed questionnaires. Data analysis through descriptive statistics and inferential statistics. The results of the study suggest (1) Disciplinary development in the teaching and learning process is in the good category with the actions taken by the principal, (2) The teacher's work ethic is in the high category viewed through several aspects, (3) There is an influence of teacher discipline development in the teaching and learning process by 21.8% on the work ethic of teachers at SDN 16 Bulu Tellue Tondong Tallasa District Pangkep District.